Two new species of Cotoneaster (Rosaceae, subgen. Chaenopetalum) for the flora of Iran - Raei Niaki, Nemat Allah; Attar, Farideh; Sheidai, Masoud; Maroofi, Hossein; Joharchi, Mohammad Reza; Ullah, Fazal (Phytotaxa, 2019)
Cotoneaster nima-yushiji and C. mazandaranicus (sect. Chaenopetalum), two new species of the genus Cotoneaster (Rosaceae) from northern Iran, are described and illustrated. Cotoneaster nima-yushiji is closely related to C. discolor Pojark. (1954: 16) but differs by larger leaves, indumentum of leaves, number of flowers per inflorescence, longer inflorescence, dark red and succulent fruit (vs. light red and non-succulent). C. mazandaranicus is morphologically similar to C. multiflorus C. A. Mey. (1831: 171), but is distinguished by foliar lamina with base narrowly cuneate to cuneate, shape and size of leaves, indumentum of leaves, color of leaves and fruit.